Spectral Shuffling with Phase Encoding and Dynamic Keys Applied to Transparent Optical Network Signals - Souza, Welerson Santos [UNESP]; Nogueira, Marcelo Pereira [UNESP]; Lage Rodrigues, Ivan Eduardo [UNESP]; Santos, Melissa de Oliveira [UNESP]; Bonani, Luiz Henrique; Aldaya, Ivan [UNESP]; Francisco Abbade, Marcelo Luis [UNESP]; IEEE (Ieee, 2020)
A recently proposed signal encryption technique consists in shuffling the samples of two or more baseband signals, which are then modulated in different optical carriers and transmitted by transparent optical networks. In this work, we aggregate two new features to this approach: phase encoding and dynamic keys (DKs). Computer simulations are used to evaluate the novel encryption scheme that provides security against chosen plaintext attacks, without introducing significant bit error rate penalties to the shuffling technique. We also verify that the DK strategy offers cryptographic diffusion.
Keywords: physical layer security; signal processing; optical communications; optical networks